FIFTH COLOMBIAN CONFERENCE OF PHARMACEUTICAL CARE: "HARNESSING THE DIGITAL REVOLUTION TO IMPROVE THE PROCESSES AND RESULTS OF PHARMACEUTICAL CARE" - FIFTH COLOMBIAN CONFERENCE OF PHARMACEUTICAL CARE (Universidad de Antioquia, 2019)
.